PLANNING OF LOADS IN THE PROCESS OF TRAINING OF HIGHLY SKILLED FOOTBALL PLAYERS - B. H. Nodirov (Web of Journals Publishing, 2024)
The process of showing special physical qualities and improving the level of training of high-skilled football players requires a lot of changes.
Keywords: Modern football, top category, training load , efficiency , pedagogical observation, sprinter running, reserve.